Condensation of Least-energy Solutions of a Semilinear Neumann Problem (Journal of Partial Differential Equations, 1995)
This paper is devoted to the study of tho least-energy solutions of a singularly perturbed Neumann problem involving critical Sobolev exponents. The condensation rate is given when n > 4 apd an asymptotic behavior result is obtained.
Keywords: Neumann problem; least-energy solutions